2008
DOI: 10.1145/1473195.1473233
|View full text |Cite
|
Sign up to set email alerts
|

Girls, computer science, and games

Abstract: An innovative week long mini-course for girls has successfully used video game development as the main motivation by teaching related computer science topics at the same time. Students split their time between creating their own game in the lab and learning about game design, usability, graphics, and artificial intelligence. They became more comfortable with the subject and say they are more likely to pursue computer science in high school because of this course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…[20] in a study of noncomputing academics found that computer skill affects computer attitude. Carmichael [21] presented a 5-day course to girls in grades 8 and 9 with a goal of motivating the students to pursue computer courses in high school or The purpose of our study was to examine experimentally whether the use of GameMaker altered college students" attitudes over the course of a semester and whether the incorporation of GameMaker into the classroom impacted students" teaching evaluations. We made the following hypotheses:…”
Section: Introductionmentioning
confidence: 99%
“…[20] in a study of noncomputing academics found that computer skill affects computer attitude. Carmichael [21] presented a 5-day course to girls in grades 8 and 9 with a goal of motivating the students to pursue computer courses in high school or The purpose of our study was to examine experimentally whether the use of GameMaker altered college students" attitudes over the course of a semester and whether the incorporation of GameMaker into the classroom impacted students" teaching evaluations. We made the following hypotheses:…”
Section: Introductionmentioning
confidence: 99%
“…Many initiatives have been introduced to support women at various stages of this pipeline (some UK examples being Computer Clubs for Girls at age 10-14 [9], and events for women undergraduates [3] and postgraduates [13]: similar events and activities exist in other countries e.g. [7]). Such initiatives have drawn criticism from a theoretical standpoint (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Like mentioned before, women and girls participation in STEM and ICT courses and careers is still significantly low. Any approach to teaching computer science to girls needs to dispel negative socio-economic and cultural stereotypes in order to make this field appealing and "cool" to them [16]. Girls compare themselves and who they are to cultural stereotypes related to the STEM fields and decide that they don't fit in.…”
Section: Learning To Code Using Serious Gamesmentioning
confidence: 99%
“…While adopting a constructionist educational approach it is important to not only focus on providing the game to students, but also providing them with the means and knowledge to develop their own games [44]. A study conducted by Carmichael [16] showcased the beneficial outcomes of combining computer science concepts with video games specifically to a young female target-group. When choosing the coding creation software the educators should consider the following series of requirements: the academic year of the students, the familiarity of the instructor(s) with coding projects, the capability of the student in creating a coding project, and the amount of time students will be spending learning the know-how to do it Alserri et al [10] have developed a conceptual model for gender-based engagement through the use of games, consisting of five elements: 1) Learning elements: these are the elements that distinguish entertainment games from educational games;…”
Section: B Examples Of Serious Games For Learning How To Codementioning
confidence: 99%